1998
DOI: 10.1074/jbc.273.6.3470
|View full text |Cite
|
Sign up to set email alerts
|

Neurabin-II/Spinophilin

Abstract: In a preceding paper, we reported a novel actin filament (F-actin)-binding protein, named neurabin, which was specifically expressed in neural tissue and implicated in neurite formation. We purified from rat brain another F-actin-binding protein, which had a domain organization similar to that of neurabin but was ubiquitously expressed, and named it neurabin-II. The original neurabin, renamed neurabin-I, had 1095 amino acids and a calculated M r of 122,729, whereas neurabin-II had 817 amino acids and a calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(115 citation statements)
references
References 30 publications
8
107
0
Order By: Relevance
“…This result, together with our previous result (Satoh et al, 1998), indicate that neurabin-II is localized at cadherin-based cell ± cell AJ both in epithelial and non-epithelial cells. In addition to their localization, neurabin-II and Ecadherin show the similar behavior in response to Rac activity, Ca 2+ concentrations and PMA.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This result, together with our previous result (Satoh et al, 1998), indicate that neurabin-II is localized at cadherin-based cell ± cell AJ both in epithelial and non-epithelial cells. In addition to their localization, neurabin-II and Ecadherin show the similar behavior in response to Rac activity, Ca 2+ concentrations and PMA.…”
Section: Discussionsupporting
confidence: 89%
“…Western blot analysis indicated that the protein level of l-afadin in MDCK cells expressing Rac1DA or Rac1DN was similar to that in wild-type cells (data not shown). We con®rmed that the accumulation of neurabin-II, but not ZO-1, was a ected by Rac activity as described (Takaishi et al, 1997;Satoh et al, 1998) (data not shown). These results suggest that there are at least two groups of proteins in cell ± cell AJ in MDCK cells: one group, including E-cadherin, b-catenin, neurabin-II, and lafadin, is sensitive to Rac activity; and the other group, including ZO-1, is insensitive to Rac activity.…”
Section: Presence Of L-afadin In Mdck Cellsmentioning
confidence: 61%
See 3 more Smart Citations